Biology of Myelomonocytic Cells 2017
DOI: 10.5772/67324
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Markers and Functional Regulators of Myelomonocytic Cells

Abstract: In this chapter, there is a description of hematopoietic stem cells, maturation curve and their differentiation into myeloid cells, including phenotypes and transcription factors involved in this process. Further, we discuss myeloid maturation curve from myeloid precursor, monoblast, premonocyte to monocytes, and also monocytes subsets regarding their CD14 and CD16 expressions and related functions in health and disease. In addition, we reason about the differentiation from monocytes either in dendritic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
1
2
0
1
Order By: Relevance
“…Monocytic lineage morphological alterations are difficult to identify and classify; in fact, monocytes do not display any visible morphological changes in MDS (1). Additionally, CD56 + and CD56 2 monocytes from MDS patients and from normal controls were not distinguishable when examined by light microscopy, in agreement with prior observations (7). However, we found that DCs derived from MDS patients' BM monocytes presented altered morphological characteristics when compared with disease-freederived iDCs and mDCs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Monocytic lineage morphological alterations are difficult to identify and classify; in fact, monocytes do not display any visible morphological changes in MDS (1). Additionally, CD56 + and CD56 2 monocytes from MDS patients and from normal controls were not distinguishable when examined by light microscopy, in agreement with prior observations (7). However, we found that DCs derived from MDS patients' BM monocytes presented altered morphological characteristics when compared with disease-freederived iDCs and mDCs.…”
Section: Discussionsupporting
confidence: 88%
“…5). Classical and intermediate circulating monocytes differ as to the phagocytic function with intermediate monocytes being more efficient in this aspect (7). Hence, we examined the frequencies of classical (CD14 hi CD16 low ) and intermediate monocytes (CD14 hi CD16 hi ) in MDS-BM samples and in control BM samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Essas propriedades as tornam alvos em terapias imunológicas, vacinação e tratamento de doenças autoimunes e inflamatórias. (41) Na linhagem monocítica, as primeiras células a serem diferenciadas são os precursores monocíticos (monoblastos), seguidos dos monócitos imaturos (promonócitos) que, ao migrarem para o sangue periférico, são denominados monócitos maduros. Quando recrutados para o sítio de inflamação os monócitos migram para os tecidos e se diferenciam em macrófagos.…”
Section: Linhagem Mieloideunclassified